Evaluation of Nutritional Status of Intensive Care Unit COVID-19 Patients Based on the Nutritional Risk Screening 2002 Score - Sedigheh Ahmadi; Donya Firoozi; Mohammad Dehghani; Morteza Zare; Zeinab Mehrabi; Maryam Ghaseminasab-Parizi; Seyed Jalil Masoumi (International Journal of Clinical Practice)
Background. Patients with COVID-19 are susceptible to malnutrition, which is particularly concerning among critically ill patients. We evaluated the Nutritional Risk Screening 2002 (NRS-2002) score in such patients and determined its relationship with the hospitalization outcome. Methods. This cross-sectional study involved COVID-19 patients admitted to the intensive care units (ICUs) of Shahid Faghihi Hospital, Shiraz, Iran, between February and March 2021. We assessed the nutritional status using NRS-2002 and determined disease severity with the APACHE II index. Demographic information, weight, height, clinical signs, previous illness, medications, biochemical test results, and history of anorexia and weight loss were recorded. Data were analyzed using SPSS version 18. Results. The mean age of 100 patients was 55.36 ± 18.86 years. According to NRS-2002, 30%, 29%, and 41% of patients were at low risk, moderate risk, and high risk of malnutrition, respectively. Age and BUN increased significantly with NRS-2002, while albumin and hematocrit followed the opposite trend (P<0.001). Patients who died had lower albumin and hematocrit levels but higher age, NRS-2002 scores, and BUN/creatinine levels than those who recovered. Multivariable logistic regression revealed that for every unit increase in the NRS-2002 score, the odds of mortality increased by 354% (OR: 4.54, CI: 1.48, 13.95, P=0.008). Conclusion. NRS-2002 is a valuable prognostic tool for critically ill COVID-19 patients, with each unit's rise in the score being associated with a 354% rise in the odds of mortality. Increased malnutrition risk was linked with higher age and BUN and lower albumin and hematocrit levels.